2020
DOI: 10.1186/s13104-020-05021-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cell liquid biopsy in selecting therapy for recurrent cutaneous melanoma with locoregional pelvic metastases: a pilot study

Abstract: Objectives: Circulating tumour cells (CTCs) from liquid biopsies provide an exceptional opportunity to obtain realtime tumour information and are under current investigation in several cancers, including cutaneous melanoma, but face significant drawbacks in terms of non-standardised methodology, low viable cell numbers and accuracy of CTC identification. In this pilot study, we report that chemosensitivity assays using liquid biopsy-derived metastatic melanoma (MM) CTCs, from 7 patients with stage IIIC, BRAF w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Although current clinical use of liquid biopsies remains limited, CTCs have been isolated from patients with a variety of tumour types [37,38], including CRC [17,18]. CTC research has evolved from prognostic studies based upon CTC enumeration, to predictive clinical response studies based upon the in vitro chemosensitivity and tumor gene expression profiles of cultured CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although current clinical use of liquid biopsies remains limited, CTCs have been isolated from patients with a variety of tumour types [37,38], including CRC [17,18]. CTC research has evolved from prognostic studies based upon CTC enumeration, to predictive clinical response studies based upon the in vitro chemosensitivity and tumor gene expression profiles of cultured CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] Moreover, the use of fresh tissues biopsies, liquid biopsies and purified circulating tumour cells in chemosensitivity and tumour gene expression assays can be used to develop more personalized locoregional or systemic treatment strategies, as recently reported. 41 With respect to locoregional chemotherapy and other therapy combinations, the use of ablative techniques, ECT, topical and intralesional therapy is under current investigation 7 , 11-14 and novel immunotherapies are increasing due to a broadening of eligibility criteria, with several clinical trials now including patients previously considered ineligible. 22 Furthermore, it has been reported that ILI with melphalan followed by systemic administration of ipilimumab provided an 85% ORR associated to increased T-cell infiltration in locoregional metastases of 26 melanoma patients, suggesting that locoregional chemotherapy administered as immune stimulant therapy could potentiate immune-responses.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show the relation between melphalan and tumour immunogenicity and suggest that in the future there may be a place for concurrent or sequential administration of systemic targeted therapies or immunotherapies with ILI. Finally, precision oncotherapy is under investigation, and drug regimens may be selected by chemosensitivity tests on purified circulating tumour cells (CTCs) obtained from liquid biopsies in individual patients [49].…”
Section: Isolated Limb Infusion As Platform To Test New Drugs and Drumentioning
confidence: 99%